Morphometry and population of preantral follicles of not pregnant Nelore cows, pregnant and fetus in the initial, medium and final third of pregnancy - Goncalves, C. G. P. [UNESP]; Tironi, S. M. T. [UNESP]; Silva, K. M. [UNESP]; Silva Junior, E. R. [UNESP]; Codognoto, V. M. [UNESP]; Souza, A. G. [UNESP]; Marques, N. F. S. [UNESP]; Brochine, S. [UNESP]; Vieira, A. F. [UNESP]; Oba, E. [UNESP] (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 2019)
The aim of this study was to describe population and morphological characteristics of preantral follicles of not pregnant cows, pregnant cows and fetus. Ten ovaries of non-pregnant Nelore cows, eighteen ovaries of pregnant cows and eighteen ovaries of fetus were used. For pregnant cows, six ovaries from each third (initial, middle and final) were evaluated, acquired from a slaughterhouse. For fetus, the same methodology and proportion of ovaries were used. Ovaries were washed, fixed and embedded in paraffin. They were then sectioned in longitudinal sections and stained by the Hematoxylin-Eosin method. Preantral follicles were classified according to morphology (primordial, primary and secondary) and degree of viability (intact and in initial, moderate and marked atresia). Descriptive and statistical analyzes were performed through KS300 image analysis program and Tukey's test. A greater proportion of primordial follicles were found in all categories. Secondary follicles were not observed in ovaries of fetus and cows in the initial third of pregnancy. All the ovary dimensions were higher in non-pregnant cows and in the final third of cows' pregnancy, and lower in final third of pregnancy fetus. It was concluded that follicle isolation was effective in describing population and morphological characteristics of preantral follicles of cows and fetus.
Keywords: bos indicus; follicular dinamic; oocyte; reproduction